1998
DOI: 10.1177/03635465980260050401
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of a Less Invasive Procedure for Reconstruction of the Ulnar Collateral Ligament of the Elbow

Abstract: A reconstruction of the anterior bundle of the ulnar collateral ligament of the elbow using bone anchors was compared regarding strain and valgus load strength with the intact ulnar collateral ligament and the reconstructed ulnar collateral ligament using bone tunnels. In both normal and reconstructed elbows, the anterior band and posterior band were tight during only a portion of the range of motion. Toward extension, the mean peak strain in the anterior band was tight for the normal and bone anchor groups, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
79
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 8 publications
6
79
3
2
Order By: Relevance
“…1,18,20,35,39,41 Of these, biomechanical testing has demonstrated that the docking technique provides the greatest resistance to valgus loading before mechanical failure. 29 Paletta et al 29 reported that the docking procedure (14.3 Nm) was nearly twice as strong as the Jobe technique (8.9 Nm) but was weaker than the native ligament (18.8 Nm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,18,20,35,39,41 Of these, biomechanical testing has demonstrated that the docking technique provides the greatest resistance to valgus loading before mechanical failure. 29 Paletta et al 29 reported that the docking procedure (14.3 Nm) was nearly twice as strong as the Jobe technique (8.9 Nm) but was weaker than the native ligament (18.8 Nm).…”
Section: Discussionmentioning
confidence: 99%
“…Next, the split native UCL ligament was reapproximated by y References 1,2,5,9,18,21,23,24,28,29,31,33,36,38 …”
Section: Testing Protocolmentioning
confidence: 99%
“…22 Hechtman et al concluded that a single injection of PRP gives significant relief in recalcitrant cases of lateral epicondylitis which is comparable to our study. 23 Gosens et al in his study, stated that the recurrence rate and need for repeated injection or surgery was also larger higher in the corticosteroid group than in the PRP group. 21 Andia et al studied thirteen prospective controlled studies, comprising of 886 patients which includes diverse tendons.…”
Section: Discussionmentioning
confidence: 87%
“…Traumatic injuries to the ulnar collateral ligament of the elbow are reasonably common in people engaged in sporting activities [5][6][7][8]. However, a traumatic avulsion fracture of the sublime tubercle of the ulnar coronoid process is an underreported injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, a traumatic avulsion fracture of the sublime tubercle of the ulnar coronoid process is an underreported injury. The ulnar collateral ligament is the elbow's primary soft tissue constraint to valgus instability [5,6,[8][9][10][11][12][13]. Inappropriate treatment of these injuries can lead to symptoms of elbow instability.…”
Section: Discussionmentioning
confidence: 99%